Landscape of Cell Communication in Human Dental Pulp. Issue 9 (16th August 2021) - Yin, Wei; Liu, Gaoxia; Li, Jinhong; Bian, Zhuan
Abstract: The cellular atlas of the stroma is not well understood. Here, the cell populations in human dental pulp through single‐cell RNA sequencing are profiled. Dental pulp stem cells, pulp cells, T cells, macrophages, endothelial cells, and glial cells are identified in human dental pulp. These cells support each other through sending growth signals. Based on the appearance of ligand–receptor pairs between two cell populations, pulp cells have the greatest communication with other cell types, while T cells have the least communication. In addition, T cells expressing TLR1, TLR2, and TLR4, and endothelial cells expressing TLR4, monitor bacterial invasion. These findings provide the census of normal dental pulp. Abstract : Pulp cells have the greatest communication in terms of quantity with other cell types, while T cells have the least communication in human dental pulp. In addition, pulp cells and dental pulp stem cells exhibit characteristic heterogeneity.